2009
DOI: 10.1186/1756-6614-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between primary hypothyroidism and metabolic syndrome and the role of C reactive protein: a cross–sectional study from South India

Abstract: Hypothyroidism is associated with metabolic syndrome and females are more at risk. Metabolic syndrome patients with a raised HsCRP are at significant risk of having sub-clinical hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
46
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 31 publications
21
46
1
1
Order By: Relevance
“…Moreover, SCH was found to be commoner than OH. Our findings with regard to incidence of SCH and OH are similar with other authors like Rezos et al, 17 Das et al, 18 and Shantha et al 19 Our study revealed that greater number of patients belonged to the urban population as compared with the rural population. Similar trend has been reported by Saxena et al 6 In the present study, a predominance of females was noted in cases of hypothyroidism.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, SCH was found to be commoner than OH. Our findings with regard to incidence of SCH and OH are similar with other authors like Rezos et al, 17 Das et al, 18 and Shantha et al 19 Our study revealed that greater number of patients belonged to the urban population as compared with the rural population. Similar trend has been reported by Saxena et al 6 In the present study, a predominance of females was noted in cases of hypothyroidism.…”
Section: Discussionsupporting
confidence: 82%
“…In terms of inflammation and thyroid, metabolic syndrome is clearly associated, for instance see Shantha et al (2009) and Ruhla et al (2010). The transition from metabolic syndrome to type 2 diabetes is a well-known risk.…”
mentioning
confidence: 99%
“…This may be important because small-for-dates (included in low-birthweight) babies are more likely to develop hypertension, diabetes and related 'metabolic syndrome' disorders in adult life (35) . Indian women tend to have small babies (36,37) and Indians are particularly prone to metabolic syndrome (36,38) , which has an association with subclinical hypothyroidism (39) and multinodular goitre in regions with iodine deficiency (20,21) .…”
mentioning
confidence: 99%